The Role of Ombudsman Scheme in Redressal of Customer Grievances - Yadav, Arvind Kumar (Journal of Commerce and Trade, 2008)
The word ombudsman originated in Sweden country in 18th century and it means a representative who protects the rights of another. According to Webster’s dictionary ‘ombudsman’ as a public official appointed to investigate citizen’s complaints against government agencies or officials that may be infringe on the rights of indivuals.Simply stated, ombudsman is an officer appointed by the legislature to handle complaints against the administrative action.The dispute resolution and justice dispensing system by Ombudsman ensures speed, economy, convenience and simplicity of procedures and maintenance of cordial relations between the parties. The system motivates and empowers customers to resolve their disputes without the help of lawyers.